2017
DOI: 10.1080/09638288.2017.1419289
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic role of motor imagery during the acute phase after total knee arthroplasty: a pilot study

Abstract: Implementing motor imagery practice into the course of physical therapy enhanced various physical outcomes during acute postoperative recovery after total knee arthroplasty. According to this pilot study, motor imagery might be relevant to promote motor relearning and recovery after total knee arthroplasty.Partial effect-sizes should be conducted in the future. Implications for rehabilitation    Adding motor imagery to physical therapy sessions during the acute period following total knee arthroplasty:    • En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 47 publications
5
61
3
1
Order By: Relevance
“…Moukarzel et al 2019 [23] Patients with total knee arthroplasty (n = 24). Four men and 20 women aged from 65 to 75 years (70 ± 2.89).…”
Section: Trial Population (Patients) Intervention Data and Target Resmentioning
confidence: 99%
“…Moukarzel et al 2019 [23] Patients with total knee arthroplasty (n = 24). Four men and 20 women aged from 65 to 75 years (70 ± 2.89).…”
Section: Trial Population (Patients) Intervention Data and Target Resmentioning
confidence: 99%
“…Few studies have investigated this topic in subjects with no past neurological history, who experience an immobilization period due to a traumatic limb injury [56,61] or in whom such immobilization is imposed for experimental reasons [4,19,57]. First, both Moukarzel et al [61] and Marusic et al [56] found some benefits of using motor simulation in rehabilitation of patients who had respectively undergone total knee and hip arthroplasty surgery. More specifically, Moukarzel et al [61] instructed patients to perform visual imagery from an internal and external perspective as well as kinesthetic imagery.…”
Section: Training the Brain To Counteract Detrimental Effects Of Tranmentioning
confidence: 99%
“…First, both Moukarzel et al [61] and Marusic et al [56] found some benefits of using motor simulation in rehabilitation of patients who had respectively undergone total knee and hip arthroplasty surgery. More specifically, Moukarzel et al [61] instructed patients to perform visual imagery from an internal and external perspective as well as kinesthetic imagery. Three 15 minute-sessions per week were provided for 4 weeks and three sets of imagery programs were devised based on the intended goals:…”
Section: Training the Brain To Counteract Detrimental Effects Of Tranmentioning
confidence: 99%
“…A recent meta-analysis investigated the benefits of OPGR and UC rehabilitation programs and showed a small to moderate, short-term beneficial effect that favors OPGR, with no longterm benefit in one-year postoperative period [47]. Different protocols of muscle strengthening have been used to counteract quadriceps weakness, such as progressive muscle strengthening [30], both high-intensity [40] and high-volume training [5], whole-body vibration exercise [48], aquatic training [49], neuromuscular electrical stimulation and the most recent non-physical approaches like action observation and motor imagery [50][51][52]. However, it is possible that current rehabilitation protocols may be inadequate, considering the type of intervention [52], its duration, included exercises, intensity volume, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the observed strength gains might be explained by alteration of both central and peripheral levels of muscle action control [59,60], with evidence of higher agonist activation [61] followed by antagonistic muscle inhibition during agonistic muscle action [62]. Therefore, incorporating MI practice in early stages of injury or surgical rehabilitation should be considered, when overt movement is restricted [50,58,61].…”
Section: Discussionmentioning
confidence: 99%